Lockdown Policies: A Macrodynamic Perspective for Covid-19 - Francesco Busato; Bruno Chiarini; Gianluigi Cisco; Maria Ferrara; Elisabetta Marzano (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The Covid-19 pandemic is producing a global health and economic crisis. The entire globe is facing the trade-off between health and recessionary effects. This paper investigates this trade-off according to a macro-dynamic perspective. We set up and simulate a Dynamic Stochastic General Equilibrium model to analyze the Covid-19 contagion within an economy with endogenous dynamics for the pandemic. There are three main results. First, the macroeconomic effects of the epidemic containment measures are much severe. The negative peak in aggregate production range from 11 percent with a soft containment measure to 35 percent with a strong containment measure; second, recovery from recession emerges when the lockdown policy is relaxed. On that basis, the output would return to its pre-lockdown level by the end of 2021; third, a return infection is expected after 36 weeks from the fist contagion contributing to exacerbates the size and duration of the economic crisis.
Keywords: E32; I12; 330; business cycle; Covid-2019 pandemic; DSGE